Outside the norm: Mental health, school adjustment and community engagement in non-binary youth. Issue 5 (July 2021) - Durbeej, Natalie; Abrahamsson, Ninnie; Papadopoulos, Fotios C.; Beijer, Karin; Salari, Raziye; Sarkadi, Anna
Aims: The aim of this study was to explore the role of self-reported non-binary gender identity in mental health problems, school adjustment, and wish to exert influence on municipal issues in a community sample of adolescents. Methods: In a cross-sectional design, data were collected through an anonymous survey in Uppsala County, Sweden, among 8385 students (response rate 58.2%) in grades 7, 9, and 11, aged 13–17 years. The Strengths and Difficulties Questionnaire (SDQ) self-report was used to assess mental health problems. Gender identity was measured with one item and youth were categorized into those who identified as male or female (i.e. binary youth), and those who did or could not identify with either gender (i.e. non-binary youth). Logistic regressions and qualitative content analysis were used to analyse data. Results: Youth with non-binary gender identity ( n = 137; 1.6%) had higher odds of having mental problems according to the SDQ total score (OR=3.05; 1.77–5.25). The association between non-binary gender identity and mental health problems remained significant after adjusting for confounders. Additionally, compared to their binary peers, the non-binary youth reported more truancy (36.5% vs 49.6%), more often failed a subject (21.5% vs 36.5%), and were more interested in exerting influence on municipal issues such as sociopolitical development, education, municipal services, and drug and alcohol policies (25.3% vs 38.0%). Conclusions: Youth with non-binary gender identity constitute a vulnerable population regarding mental health problems and school adjustment. The willingness to exert influence on municipal issues suggests a possible pathway to engagement.